Daily Temporal Associations Between Physical Activity and Symptoms in Multiple Sclerosis. Issue 1 (25th April 2018) - Kratz, Anna L; Fritz, Nora E; Braley, Tiffany J; Scott, Eric L; Foxen-Craft, Emily; Murphy, Susan L
Abstract : People with multiple sclerosis reduced physical activity following periods of high fatigue and depressed mood. In contrast, higher than usual physical activity was followed by improved fatigue and mood. Abstract: Background: Symptom severity is negatively associated with physical activity in multiple sclerosis (MS). However, it is unclear how physical activity and symptoms correlate on a day-to-day basis in persons with MS. Purpose: To determine the temporal within-person associations of pain, fatigue, depressed mood, and perceived cognitive function with physical activity in MS. Methods: Ambulatory adults with MS ( N = 107) completed 7 days of home monitoring. Continuous physical activity data (assessed via wrist-worn accelerometer) and concurrent ecological momentary assessment (5X/day) of pain, fatigue, depressed mood, and perceived cognitive function were collected. Data were analyzed using multilevel mixed modeling. Results: Fatigue and depressed mood demonstrated bidirectional associations with physical activity, whereas pain and cognitive function did not. Higher than usual fatigue ( B = −5.83, p = .001) and depressed mood ( B = −4.12, p = .03) were followed by decreased physical activity. In contrast, higher than usual physical activity was associated with subsequent decline in fatigue ( B = −0.001, p = .02) and depressed mood ( B = −0.0007, p = .02); however, the association between physical activity and fatigue varied across the day. Conclusions: Physical activity is dynamically related to fatigue and mood on a moment-to-moment basis in MS. Efforts to increase physical activity in MS must incorporate a focus on how symptoms affect and are affected by activity.